Narrative Review of Patient Cancer Tissue–Derived Zebrafish Xenograft Models for Evaluating Drug Sensitivity as an Avatar Model for Clinical Application - Yusuke Sugino; Xin Bao; Takumi Kageyama; Sho Sekito; Shiori Miyachi; Takeshi Sasaki; Toshio Tanaka; Takahiro Inoue (Cancer Medicine, 2025)
ABSTRACT In the pursuit of optimal medical care, treatment selection based on the molecular analysis of genomes, transcriptomes, and proteomes has been explored; however, this approach relies on data from large patient groups, resulting in limited accuracy in predicting treatment efficacy. Diseases involve complex pathological networks, requiring treatments that target multiple key molecules in these networks. Drug screening using these networks, which cannot be achieved through a gene expression analysis alone, requires animal models. Zebrafish embryos have an immature immune system, allowing for a high engraftment rate of human cancer cells transplanted within 48 h after fertilization. Consequently, the time required for engraftment is also reduced. Less than 500 human cancer cells are required for transplantation, enabling the assessment of drug efficacy from clinical samples within approximately 1 week. The cost of raising zebrafish is low, drug efficacy can be evaluated using small amounts of drugs, and their use aligns closely with animal welfare standards. This review aims to discuss the technical aspects of evaluating drug efficacy using zebrafish patient cancer tissue–derived xenograft (zPDX) models and summarize previous studies using zPDX as an avatar model for personalized medicine.